2016
DOI: 10.1016/j.polymer.2016.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and structural response of in situ prepared biobased poly(ethylene 2,5-furan dicarboxylate) nanocomposites

Abstract: Polymer is an interdisciplinary journal dedicated to publishing innovative and significant advances in Polymer Physics, Chemistry and Technology. We welcome submissions on polymer hybrids, nanocomposites, characterisation and self-assembly. Polymer also publishes work on the technological application of polymers in energy and optoelectronics. The main scope is covered but not limited to the following core areas: Polymer Materials Nanocomposites and hybrid nanomaterials Polymer blends, films, fibres, networks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 64 publications
3
61
0
Order By: Relevance
“…The first two polyesters (PEF, PPF) show excellent gas barrier, mechanical and thermal properties, superior than those of the corresponding polyesters based on terephthalic acid, poly(ethylene terephthalate) (PET), and poly(propylene terephthalate) (PPT) . There exist few studies on copolymers and nanocomposites based on PEF, PPF, and PBF, as well as a few PAFs . Surprisingly, blends of these compounds attracted much less attention (to the best of our knowledge, only two studies reported on PBF/PLA blends).…”
Section: Introductionmentioning
confidence: 99%
“…The first two polyesters (PEF, PPF) show excellent gas barrier, mechanical and thermal properties, superior than those of the corresponding polyesters based on terephthalic acid, poly(ethylene terephthalate) (PET), and poly(propylene terephthalate) (PPT) . There exist few studies on copolymers and nanocomposites based on PEF, PPF, and PBF, as well as a few PAFs . Surprisingly, blends of these compounds attracted much less attention (to the best of our knowledge, only two studies reported on PBF/PLA blends).…”
Section: Introductionmentioning
confidence: 99%
“…Gas barrier, mechanical properties, thermal stability, and crystallization rates of polyesters can be also enhanced with the addition of nanofillers. In the case of PEF, it was reported that the presence of the clays slightly accelerated the polyester crystallization behavior, while from thermogravimetric analysis (TGA) it was found that nanocomposites have higher thermal stabilities than pure PEF . However, as was found in PET, these can affect the molecular weight increase during SSP .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of a series of furan-based copolymers has been reported in literature [43][44][45][46][47][48][49][50]. Furthermore, some recent works reported PEF, PPF and PBF nanocomposites [51][52][53][54][55]. The third way, that is, blending, is an easy and feasible way for modifying polymer properties.…”
mentioning
confidence: 99%